Status and trends in coastal fishery resources of Sarawak, Malaysia - a focus on tropical deltaic estuary - Mustafa, M. Golam; Hamli, Hadi; A. Rahim, Khairul Adha; Rajaee, Amy H. (Bioflux SRL, 2021)
The sustainable use of fisheries resources is a major concern for coastal resource management. Malaysia is endowed with vast coastal fisheries resources which contribute about 1% to national GDP. Sarawak is the major state of Malaysia having high potentials for coastal fisheries. This study was conducted from December 2018 to May 2019 to inquire the status of the coastal fisheries and to identify gaps for further research and measures for sustainable fisheries. The study was undertaken through desk-based review and analysis of secondary data along with a focus on the primary fish landing data collected directly from fishers’ catches and Gnian (type of Estuarine Set Bag Net-ESBN) fish sampling. FAO production data (1950-2011) for fishing zone 71 (data of Sarawak-Sabah fishing zone) showed a sharp incremental trend (70100 to 682004 MT; R = 0.992). According to DoF data from 2000 to 2016, the Sarawak fishery was mainly contributed by coastal catches which is about 70% of the total catch, and a clear monthly fluctuation was observed in fish catches from Sarawak coast. In the same dataset (DoF 2000-2016), there was constant landing from March to August whereas declining trends from September to February. Data from case study site (Daro) exhibited 40.9 MT catch in 2018 and varied every month from the lowest 3004 kg (November) to the highest 3693 kg (March). Fishing efforts in terms of fishermen, vessels and gears were steadily increased over the period of year 2000 until 2016. The main contributing species/groups by weight were prawn and shrimp (39%) followed by Bornean grenadier anchovy (15%), and eeltail catfish, crabs and Gangetic anchovy (4%). There were 78 contributing species/group/guilds including fresh water, estuarine and coastal fishes showed in historic database of Daro via the catch assessment forms. However, there were only 34 species found to be contributing to catch during 2018. Out of 34 species, 23 were found contributing regularly (12 months) whereas the other 11 species were found contributing seasonally to catch. The study during surveys in Daro in April 2019 discovered 27 species. The ecological variation in seasonal pattern might be the driving factor for these species contributing variation to catch.